Comparative effectiveness of surgery and radiosurgery for stage I non–small cell lung cancer. Issue 14 (6th April 2015) - Yu, James B.; Soulos, Pamela R.; Cramer, Laura D.; Decker, Roy H.; Kim, Anthony W.; Gross, Cary P.
Abstract : BACKGROUND: Although surgery is the standard treatment for early‐stage non–small cell lung cancer (NSCLC), stereotactic body radiotherapy (SBRT) has been disseminated as an alternative therapy. The comparative mortalities and toxicities of these treatments for patients of different life expectancies are unknown. METHODS: The Surveillance, Epidemiology, and End Results–Medicare linked database was used to identify patients who were 67 years old or older and underwent SBRT or surgery for stage I NSCLC from 2007 to 2009. Matched patients were stratified into short life expectancies (<5 years) and long life expectancies (≥5 years). Mortality and complication rates were compared with Poisson regression. RESULTS: Overall, 367 SBRT patients and 711 surgery patients were matched. Acute toxicity (0‐1 month) was lower from SBRT versus surgery (7.9% vs 54.9%, P  < .001). At 24 months after treatment, there was no difference (69.7% vs 73.9%, P  = .31). The incidence rate ratio (IRR) for toxicity from SBRT versus surgery was 0.74 (95% confidence interval [CI], 0.64‐0.87). Overall mortality was lower with SBRT versus surgery at 3 months (2.2% vs 6.1%, P  = .005), but by 24 months, overall mortality was higher with SBRT (40.1% vs 22.3%, P  < .001). For patients with short life expectancies, there was no difference in lung cancer mortality (IRR, 1.01; 95% CI, 0.40‐2.56). However, for patients with long life expectancies, there was greater overall mortality (IRR, 1.49; 95% CI, 1.11‐2.01) as well as a trend toward greater lung cancer mortality (IRR, 1.63; 95% CI, 0.95‐2.79) with SBRT versus surgery. CONCLUSIONS: SBRT was associated with lower immediate mortality and toxicity in comparison with surgery. However, for patients with long life expectancies, there appears to be a relative benefit from surgery versus SBRT. Cancer 2015;121:2341–2349. © 2015 American Cancer Society . Abstract : For elderly patients, outcomes from surgery and stereotactic body radiotherapy for stage I non‐small cell lung cancer differ by a patient's overall life expectancy. For patients with short life expectancy, stereotactic body radiation is preferred as it has fewer side effects.